Analysis and Comparison of Micro Frontend and Monolithic Architecture for Web Applications - Hidayat, Dwiky Chandra; Atmaja, I Ketut Jaya; Sarasvananda, Ida Bagus Gde (Jurnal Galaksi, 2024)
A robust system to support the learning aspect is a major concern at PT Bina Taruna Wiratama, a technology-based education company. To achieve this goal, the technology team is required to be able to develop the system quickly and with minimal bugs. Various aspects affect the programmer's ability to produce a high-quality system that is easy to develop further. One of the key aspects is system architecture, which serves as the initial foundation of a system. Currently, the frontend application is still developed as one large application, which causes the build time to be quite long, which is around 30-50 minutes. To overcome this problem, the author explores techniques that can be applied in frontend application development, one of which is the use of micro frontend architecture with run-time integration techniques. This study aims to evaluate how the implementation of micro frontend architecture can be applied to the Smart BTW application and to understand the advantages and disadvantages of the architecture. The implementation results show that the sub-project application can use different JavaScript framework versions, with a faster build time, on average 1-2 minutes, although the initial load is slightly longer, which is 2-3 seconds compared to the monolithic architecture.